POLYGAMY IN THE PERSPECTIVE OF THE CHRISTIAN FAITH AND ITS IMPLICATIONS FOR TEACHING PAK TEACHERS - Elieser R. Marampa' (Institut Agama Kristen Negeri Kupang, 2021)
The practice of polygamy is a common thing among the general public such as Christians, Muslims, Hindus and Buddhists as well as among other religions, polygamy is a very significant family problem. In terms of Christian faith, polygamy is one of the problems that is very contrary to true marriage. Marriage is a family institution that was created by God from the beginning, namely before humans fell into sin, starting with the first family, namely Adam and Eve. It is clear that in Christian teachings, polygamy is a behavior that is prohibited in everyday life, especially in the family. Polygamy is having more than one wife. While the Bible does not teach a husband to have several wives. God does not want marriage more than one wife (Genesis 2:24) states that a man will be united with his wife so that the two of them will become one flesh. In obtaining data, the author uses a literature research study, which is to explore various literatures in depth and analyze the data descriptively to find out the real situation. Keywords: Polygamy, Christian Faith, Christianity Today